India and South Korea’s growing synergy: from economic to a strategic focus (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
India and South Korea have witnessed a steadily growing synergy in recent years, shifting their focus from economic cooperation to a more strategic partnership. This evolving relationship is based on shared democratic values, economic interests, and geopolitical considerations. Investments have also played a crucial role in deepening the economic ties between India and South Korea. South Korean companies like Samsung, Hyundai, and LG have made significant investments in India, contributing to job creation and technology transfer. In return, Indian companies have invested in South Korea’s information technology and pharmaceutical sectors. In recent years, the focus of the India-South Korea relationship has expanded beyond the economic realm to include strategic aspects. Both countries have recognized the need to collaborate on security issues in the Indo-Pacific region, given the increasing assertiveness of China and North Korea's nuclear ambitions. India and South Korea’ growing synergy, shifting from economic to strategic focus, underscores the changing dynamics of their relationship. This evolving partnership has the potential to contribute significantly to regional peace, stability, and economic development.